Kokoviljasäilörehu osana nurmituotantoon liittyviä suunnitelmia - Turunen, Harri (Maatalouden taloudellinen tutkimuslaitos, 1999)
Nautakarjatiloilla rehuviljan tuotanto tapahtuu suhteellisen pienissä yksiköissä eikä se nykyisillä viljan hinnoilla ole kovin taloudellista. Lisäksi eräät viimeaikojen tukiratkaisut ovat hieman parantaneet nurmirehun asemaa viljaan verrattuna. Nautakarjatilojen puimuri-investoinneista päätellen omaa rehuviljaa tuotetaan jatkossa yhä harvemmalla tilalla. Aktiivitiloille tehdyn kyselyn perusteella vain yksi maitotila sadasta aikoo hankkia ajopuimurin lähivuosina. Myös yhä useampi viljelijä vähentää rehuviljan suhteellista alaa, luopuu rehuviljan viljelystä tai on epävarma koko tilan tulevaisuuden suhteen. Koska useilla nautakarjatiloilla tukiehtojen mukainen lannankäyttö koetaan ongelmaksi jo nyt, viljan jääminen pois viljelykierrosta vaikeuttaa tilannetta yhä enemmän. Nurmirehuntuotannossa keskeisimpiä ongelmia ovat nurmen uudistamisen, viljelykasvivalinnan ja lannankäytön yhteensovittaminen. Rehuviljaa korvaavaksi vaihtoehdoksi viljelykierrossa on esitetty kokoviljasäilörehua, jossa on mukana koko kasvusto eli jyvät, lehdet ja korsi. Tällä menetelmällä päästäisiin yhteen peltoviljelyn koneketjuun ja vältettäisiin rehuviljan puintiin ja kuivatukseen liittyvät työ- ja pääomakustannukset. Kokoviljasäilörehun viljelyä, tuotantotekniikkaa, ruokintavaikutuksia ja taloudellista kannattavuutta selvitetään usean tutkimuslaitoksen yhteistyönä. Selvitettävänä on, voidaanko nautakarjatiloilla perinteinen rehuviljanviljely korvata ja nurmet uudistaa viljakasvustolla, josta tietyssä kehitysvaiheessa tehdään säilörehua. Tyypillisillä maitotiloilla siirtyminen viherlinjaan muuttaa viljelykiertoa ja karjalannan käyttömahdollisuuksia. Kun rehuvilja ostetaan tilan ulkopuolelta, eläinmäärien ja nurmi- ja kokoviljarehun tuotannon sekä lannankäytön välille joudutaan hakemaan uusi ympäristönormit huomioon ottava tasapaino.

This study is concerned with the current state, problems and plans for the near future related to the cereal and grass production on cattle farms. Production has been examined on the basis of the proportional shares of cereal and grass fodder area as well as farmers intentions concerning changes in fodder production. The study also covers the current state and future prospects of farming, and it is based on mailed questionnaires directed at the farms participating in the profitability bookkeeping of the Agricultural Economics Research Institute in spring 1999 as well as DataLaari farm panel made by the Food Facts Ltd. in 1998. Both inquiries concern the situation after autumn 1998, i.e. following an exceptionally bad crop year. About half of the cattle farms plan to continue fodder production in the current extent and with the same proportional shares of grass and cereal fodder. The willingness to continue production is the highest on bookkeeping farms practising cattle husbandry, while farms that participated in the farm panel expressed more intentions related to changes in fodder production due to uncertainty or plans to quit production. In terms of the different parts of the country as well as active farms and the farm panel, the intentions to change fodder production deviate mainly for the part of Ostrobothnia, where uncertainty was more common and many farms refused to participate in the study. The planning of the fodder production is particularly difficult due to the uncertainty related to the EU membership as well as the Agenda 2000 process, which was underway when the inquiry was made. About half of the farms consider that Agenda 2000 will have no effect on their fodder production, but almost a fifth of all cattle farms were unable to estimate the future of their fodder production or did not answer the questions. About half of the bookkeeping farms practising cattle husbandry expects the efficiency of arable crop production to continue to decrease, and according to about a quarter the cereal area is going to fall as a result of Agenda 2000. Whole cereal, i.e. cereals where part of the straw and the whole ear is used as fodder, was cultivated for either green fodder or silage on about a quarter of dairy farms participating in the bookkeeping in 1999. On other cattle farms whole cereal was not produced at all. On dairy farms producing whole cereal the average area under this was a little over four hectares. The farms expressed no intentions to increase the area of whole cereal, and the introduction of whole cereal fodder was considered on very few of the farms where cattle husbandry was based on grass fodder only. The use of whole cereal fodder is examined in a joint project, primarily between the Agricultural Research Centre and Agricultural Economics Research Institute. An economic study will be published in the beginning of 2000 concerning the comparison of the milk production cost at the farm level between whole cereal and grass feeding.
Whole cereal silage as part of plans conserning grass production
Keywords: Ma; Suomi; maatalous; maataloustuotanto; kokoviljasäilörehu; agriculture; production; whole cereal silage; Finland